AKULTURASI BUDAYA TIMUR TENGAH KE INDONESIA DAN PENGARUHNYA DALAM KESUSASTRAAN (STUDI KASUS PADA SERAT CENTHINI) - Siti Muslifah (CMES (Center of Middle Eastern Studies), 2013)
Cultural acculturation and syncretism is indicated to occur and has great influenceon Javanese socio-cultural values, and also on arts and literature fields. In Javaneseliterature, Serat Centhini is a masterpiece written by great Javanese poet. PakubuwanaV, when he was a prince of Kasunanan Palace. It is not only presenting Javaneseknowledge comprehensively but also containing very strong Islamic values. The Islamicvalues contained in the Javanese literature masterpiece are, among the others, religiousproselytizing, Islamic syar’i, Islamic pillars and oneness of God. The presence of Islamicvalues in Javanese literature is a proof of Middle-East cultural acculturation inIndonesia, especially in literature area.